Efeito do envelhecimento em baixa temperatura nas propriedades de aços inoxidáveis lean duplex - Silva, Rodrigo da (2016)
In this work, the mechanical and corrosion properties of two lean duplex steels (LDSS) 2101 and 2404 aged at 475 °C for up to 2000 h were assessed, and the obtained results were compared with the standard duplex stainless steel (DSS) 2205. The microstructural changes were analyzed by means of optical microscopy (OM), X ray diffraction (XRD), measured by ferritescope and transmission electron microscopy (TEM). The mechanical properties were assessed based on Vickers microhardness measurements and Charpy impact tests. The corrosion resistance was assessed by double loop electrochemical potentiokinetic reactivation (DL-EPR), anodic polarization in 3.5% NaCl solution and immersion tests in ferric chloride solution. The analysis by optical microscope and X ray diffraction of the samples solution treated and aged for 2000 h of the studied materials do not reveal microstructural change as a function of thermal aging. However, the measurements by ferritescope show a decrease in magnetic permeability of the ferrite with the extension of aging time for 2000 h. TEM analysis of the samples aged for 2000 h show that the formation of α’ phase occurs in all materials. However, precipitation of G phase is much greater in the AID 2205. Hardness measurements show that the hardening effect caused by the formation of α’ phase is higher in DSS 2205. On the other hand, impact tests show that the LDSS 2404 has the smaller impact toughness property of the studied alloys as a function of thermal aging. DL-EPR results show that the LDSS 2101 has the greater degree of Cr depletion with aging for 2000 h. Anodic polarization measurements of the materials studied show that the thermal aging for 2000 h promotes a decrease in Epit, causing an increase in the density and size of pits. Immersion tests in ferric chloride solution showed a higher corrosion rate for the DSS 2205 as a function of aging time for 2000 h